Isolation and evaluation of biological characteristics of lactic acid bacteria from Ben Tre fermented pork - Nguyễn, Ngọc Thạnh; Trần, Thị Thùy Dương; Lưu, Minh Châu; Bùi, Hoàng Đăng Long; Nguyễn, Văn Thành; Đoàn, Thị Kiều Tiên; Huỳnh, Xuân Phong (Hue University Journal of Science: Natural Science, 2026)
Fermented pork (nem chua) is a traditional product and a rich source of lactic acid bacteria (LAB) with probiotic potential. This study aimed to isolate and evaluate key biological properties of LAB from Ben Tre fermented pork, including lactic acid production, GABA biosynthesis, and probiotic potential in terms of acid tolerance and autoaggregation. A total of 20 LAB strains were isolated from 5 fermented samples during 5 days of fermentation, with the highest lactic acid concentration (25.54 g/L) observed on day 3. In MRS medium supplemented with 3% (w/v) monosodium glutamate (MSG), all strains were capable of producing γ–aminobutyric acid (GABA) after 2 days of incubation, with concentrations ranging from 1.24 to 3.24 mg/mL. The eight strains with the highest GABA biosynthesis capacity were selected for probiotic evaluation. Among them, only NA1.3 strain survived at pH 2, while all strains remained viable at pH 3, with NA2.4 strain showing the highest bacterial density (7.05 log CFU/mL) after 3 h. Regarding autoaggregation ability, PD1.4, NA2.4, and NA1.3 exhibited the highest autoaggregation rates (19.99–21.48%). These findings indicate that NA1.3 strain is a potential candidate for future applications in fermented pork production.